Qualitative assessment of infant sleep practices and other risk factors of sudden infant death syndrome (SIDS) among mothers in Lusaka, Zambia - Godwin K. Osei-Poku; Lawrence Mwananyanda; Patricia A. Elliott; William B. MacLeod; Somwe Wa Somwe; Rachel C. Pieciak; Arnold Hamapa; Christopher J. Gill (BMC Pediatrics, 2023)
Abstract Background There is very little information on the beliefs and perceptions of mothers about SIDS and its related risk factors in Africa. To better understand parental decisions about infant sleep practices and other risk factors for SIDS, we conducted focus group discussions (FGDs) with mothers of infants in Lusaka, Zambia. Methods FGDs involved 35 purposively sampled mothers aged 18–49 years. FGDs were conducted using a semi-structured interview guide in the local language, Nyanja. These were translated, transcribed verbatim into English, and then coded and analyzed using thematic analysis in NVivo 12. Results Six FGDs were conducted with 35 mothers in April-May 2021 across two study sites. FGD Participants were generally aware of sudden unexplained infant deaths, with several describing stories of apparent SIDS in the community. The side sleeping position was preferred and perceived to be safer for the infant with most believing the supine position posed an aspiration or choking risk to the infant. Bedsharing was also preferred and perceived to be convenient for breastfeeding and monitoring of the infant. Experienced family members such as grandmothers and mothers-in-law, and health care workers were frequently cited as sources of information on infant sleep position. A heightened awareness of the infant’s sleeping environment was suggested as a mechanism to prevent SIDS and smothering. Conclusions Decisions about bedsharing and infant sleep position were guided by maternal beliefs and perceptions about what is convenient for breastfeeding and safer for the infant. These concerns are vital to designing tailored interventions to address sleep-related sudden infant losses in Zambia. Public health campaigns with tailored messages that address these concerns are likely to be effective at ensuring optimal uptake of safe sleep recommendations.